Clinical Utility of Colonoscopy in Young Patients with Rectal Bleeding in Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Rectal bleeding is a very common symptom. Intermittent passage of small amount of bright red blood from rectum is a clinical problem frequently found in patients of all ages. It’s often attributed by the patients to ‘piles’ and indeed haemorrhoids or piles are a common cause of this symptom. However, there are other causes and it is important to know what the possible causes are and how to investigate the symptom further. The type and amount of bleeding as well as the age of the patient are important in the initial assessment of the bleeding. Colonoscopy is the investigation of choice for establishing a diagnosis and treatment. In the current study, we aimed to study clinical utility of colonoscopy in young patients with chronic LGI bleeding.Material and methods: This prospective observational study was conducted between May 2010 to December 2010 at Department of Gastrointestinal, Hepatobiliary and Pancreatic Disorder (GHPD) of BIRDEM General Hospital, Dhaka, Bangladesh including all consecutive patients with age less than 40 years, presenting with per rectal bleeding of duration more than 4 weeks.Results: A total of 396 colonoscopies were performed in patients with age less that 40 years, of them 103 were enrolled in this study as per inclusion and exclusion criteria. The mean age of study population was 28.19 (SD 10.01, range 3 -40) years with 34 (33%) females. In majority of patients chronic LGI bleed was present for more than 6 months. Of them, 29 (28.2%), 16 (15.5%) and 9 (8.7%) had history of LGI bleed for 7 – 12 months, 13 – 24 months and more than 25 months respectively. Remaining 44 (42.7%) had LGI bleed for 6 months. Intermittent per rectal bleeding was present in 97 (94.2%), remaining 6 patients (5.8%) complained of daily rectal bleeding. Colonoscopy was attempted in 103 patients, with cecal intubation rate of 98.1% (101/103). The diagnostic yield was 91.26% (94/103). Anorectal region was most common site for the lesion (50/94, 53.19%). Six patients (6.38%) had proximal colonic lesions and pan colonic lesions each. Hemorrhoids in isolation (29/94, 30.85%) or in combination of other lesions (16/94, 17.02%) was most common colonoscopic finding.Conclusion: Rectal bleeding is a symptom to be considered carefully, since it can be associated with malignancy. Since neoplastic and non-neoplastic disease may coexist, it is controversial as to whether chronic rectal bleeding in the young patients requires colonoscopy as a first line investigation. The optimal approach to young patients is not known. Colonoscopy is a valuable diagnostic tool and can help to establish the source of rectal bleeding in young patients.Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 37-40